NCAPD3‐mediated AKT activation regulates prostate cancer progression - Yi Zhang; Wanlin Xie; Xicui Zong; Yuanyuan Fang; Jia Ren; Zuolei Jing; Yong Wei; Shan Lu; Qingyi Zhu; Ping Liu (FASEB BioAdvances)
Abstract Despite therapeutic improvements in prostate cancer treatment, the recurrence and mortality rates are still high, and the underlying mechanisms still need further study. Non‐SMC Condensin II Complex Subunit D3 (NCAPD3) is a subunit of condensin II complex, mainly involved in the mitotic chromosome condensation of cells. This study aimed to figure out the detailed mechanisms by which NCAPD3 contributed to prostate cancer development. Clinical samples and cell lines were used to measure the expression of genes by quantitative real‐time RT‐PCR (qRT‐PCR), Western‐blot assay (WB), immunohistochemistry (IHC), and immunofluorescence (IF). Chromatin immunoprecipitation quantitative PCR (ChIP‐qPCR) and dual‐luciferase reporter assays were examined to explore the interplays between molecules. CCK8, transwell, and wound‐healing assays were applied to perform cell proliferation and migration. A subcutaneous tumor xenograft model was constructed by injecting DU145‐Lv‐NCAPD3 cells and control cells into male BALB/c nude mice to confirm the result derived from in vitro assay. NCAPD3 increased STAT3 expression and phosphorylation in PCa cells, thereby enhancing STAT3 transcriptional activity to improve the levels of JAK2 and EZH2. This led to an increase in phosphorylation of AKT at Thr 308 and Ser 473 through JAK2/PI3K and EZH2/NSD2/mTORC2 pathways, respectively. Moreover, there was a positive mutual activation between STAT3 and JAK2, further enhanced by NCAPD3 to promote PCa progression. NCAPD3, as an oncogene, promoted PCa progression by phosphorylating and activating AKT, which suggests a novel functional pathway of NCAPD3 in promoting PCa progression.